NGOs, partnerships, and public-private discontent in Nepal’s health care sector (Medicine Anthropology Theory, 2018)
Public-private partnerships (PPPs) have become increasingly popular models of collaboration in the global health arena to deliver, scale, and evaluate health care services. While many of these initiatives are multicountry, large-scale partnerships, smaller NGOs play increasingly central roles in new forms of privatization. This article draws on our collective experiences working in a PPP between the nongovernmental organization Possible and the Ministry of Health in Nepal to ethnographically examine the fragile and contested nature of these arrangements in the Nepali context, amidst an increasingly privatized health care landscape that is resulting in widespread discontent and distrust throughout the country, as well as financial hardship. We discuss the Possible PPP as one approach that simultaneously seeks to strengthen public-sector health care systems, yet still taps into some of the promises, anxieties, and blind spots – such as the broader social determinants of health – inherent in new forms of public-private global health work.